Microstructural investigation and mechanical properties of Al2O3-MWCNTs reinforced aluminium composite - Salleh, Mohd Shukor; Abd Rahim, Mohammad Na’aim; Yahaya, Saifudin Hafiz; Subramonian, Sivarao; Abdul Rashid, Azrin Hani; Syed Ahmad, Syarifah Nur Aqida; Al-Zubaidi, Salah Salman (AIMS Press, 2025)
Hybrid reinforcement of metal matrix composites (MMCs), particularly those based on aluminum, is widely recognized for resulting in excellent mechanical properties, such as high strength-to-weight ratio, enhanced wear resistance, and superior thermal conductivity. In this study, multi-wall carbon nanotubes (MWCNTs) and alumina (Al2O3) were used as the reinforcement for aluminum A356 via electromagnetic stirring (EMS). The composite was fabricated by varying the Al2O3 and MWCNT contents. Molten MMCs were then poured into the mold, and samples were collected after solidification. The effect of hybrid reinforcement by EMS on the distribution of microstructure and mechanical properties was investigated. Optical microscopy (OM) revealed that the presence of Al2O3-MWCNTs as reinforcement refined the grains, evolving from dendritic to rosette. The grains became closely packed, and reduced porosity was observed. The intermetallic phases in the composite were identified using secondary electron imaging–field emission scanning electron microscope (SEI–FESEM) and X-ray diffraction (XRD). Mechanical properties of the matrix were measured using a universal testing machine and a Vickers hardness test. The results indicate that the 319 AIMS Materials Science Volume 12, Issue 2, 318–335. reinforcement percentage and stirring time significantly impact mechanical properties. The best properties were obtained with 0.5 wt% MWCNT, 6 wt% Al2O3, and 10 min of stirring. Under these conditions, the highest values for yield strength (94 MPa), tensile strength (221 MPa), elongation at break (11.37%), and hardness (89 HV) were achieved. These findings show that an optimum amount of reinforcement content and stirring time greatly influence the mechanical properties of the composite. The results show that the EMS effectively overcomes common challenges associated with hybrid metal matrix composites, namely proper particle distribution, reduced porosity, and enhanced mechanical properties. EMS provides a practical solution for producing high-performance aluminum composites suitable for structural and thermal applications with lower costs.